2016
DOI: 10.1108/jgr-07-2016-0017
|View full text |Cite
|
Sign up to set email alerts
|

Work–life balance: how can we help women IT professionals in Morocco?

Abstract: Purpose The present study aims to understand how Moroccan women working in information technology (IT) perceive the roles they fulfill in both their private and professional lives and assess their Work–life balance (WLB). Design/methodology/approach Existing research about WLB in Morocco focuses mainly on the public sector. As the present study is the first of its kind to deal with the private sector and more specifically IT, it is exploratory in nature while adopting a qualitative methodology. Twenty Morocc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 12 publications
3
25
2
2
Order By: Relevance
“…(Lawson et al, 2013;Gupta, 2012) In the context of organizations and people, work life balance has demonstrated its significance since the past decades. Work life balance has indeed been found to be the major factor in the productivity improvement of employees and this has a positive impact on the general performance of organizations (Semlali and Hassi, 2016). An organization needs to implement effective work-life balance policy, that is, a policy that allows employees to remain socially connected with society while cost and turnover are controlled, and productivity improved (Helmle et al, 2014).…”
Section: Work-life Balance and Employee Performancementioning
confidence: 99%
See 1 more Smart Citation
“…(Lawson et al, 2013;Gupta, 2012) In the context of organizations and people, work life balance has demonstrated its significance since the past decades. Work life balance has indeed been found to be the major factor in the productivity improvement of employees and this has a positive impact on the general performance of organizations (Semlali and Hassi, 2016). An organization needs to implement effective work-life balance policy, that is, a policy that allows employees to remain socially connected with society while cost and turnover are controlled, and productivity improved (Helmle et al, 2014).…”
Section: Work-life Balance and Employee Performancementioning
confidence: 99%
“…In this regard, balance is achieved when there is harmony between work and life. (Semlali and Hassi, 2016) Since the last decades, the concept of Work-life Balance has been viewed as crucial to both organizations and people, and it has indeed been found to greatly contribute in the improvement of productivity of employees which in turn impacts the performance of organizations in positive manner (Guthrie, 2012). Effective policy of work-life balance embraced by the organization allows the employees to socialize with the community while assuring that cost and turnover are under control and productivity is improved (Helmle et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…From the literature review, Sheikh et al (2018) found that work demands and home demands cause significant effects on work-life balance. In the work of Semlali and Hassi, (2016), it was found that balance is achieved when there is harmony between work and life. Aziz and Chang (2013) claimed that work and family demands effect significantly on work-life balance.…”
Section: Hypothesesmentioning
confidence: 99%
“…As women have to look after their children and at the same time, have to fulfill their domestic responsibilities, it often creates a barrier for their career advancement (Sharma & Parmar, 2016;Cross and Linehan, 2006). Balancing both workplace and family is difficult for women since giving time to kids, spouse and office are their expected social behavior (Semlali, & Hassi, 2016). A study conducted by Goyal (2014) showed that 75% of the female doctors reported that they have less time for their children while 44% of the doctors have given preferences to household work indicating that the importance of household work cannot be underestimated.…”
Section: Literature Reviewmentioning
confidence: 99%